Pengaruh Beban Kerja, Stress Kerja terhadap Kinerja Pegawai Dengan Motivasi sebagai Variabel Moderasi pada Badan Keuangan Daerah Kabupaten Kayong Utara - Susanti, Nining Eka; Hadiyati, Ernani; Hendrakusuma, FX Bhakti; Gunadi, Gunadi (SENTRI: Jurnal Riset Ilmiah, 2025)
This study aims to analyze the influence of workload and job stress on employee performance, with work motivation as a mediating variable at the North Koyong Regional Finance Agency. The study used a causal associative approach, with a population of 42 employees of the North Koyong Regional Finance Agency, and a saturated sampling technique. The sampling technique used a questionnaire and data analysis using SmartPLS. The results showed that workload did not significantly influence employee performance, indicating that a high workload does not necessarily directly increase or decrease performance. Work stress also did not significantly influence employee performance, indicating that work pressure is still tolerable by employees. In addition, workload did not significantly influence work motivation, indicating that a high workload is unable to generate internal drive to work better. Conversely, work stress was shown to have a positive and significant effect on work motivation, where certain pressures can be a driving force for increased motivation if perceived as challenges. Work motivation itself significantly influences employee performance, confirming that motivated employees tend to show more optimal performance. However, work motivation was unable to significantly mediate the relationship between workload and job stress on employee performance, indicating that motivation's role as an intermediary is still not optimal.